Chalo Jahaji: On a journey through indenture in Fiji - V. Lal, Brij (ANU Press, 2012)
"It is a milestone in subaltern studies, a biographical journey penned by a living relic of the indentured experience and a scholar whose thoroughly interdisciplinary approach is a good example for the anthropologist, the sociologist or the economist who wish to see the proper integration of their disciplines in a major historical work." Brinsley Samaroo, University of the West Indies, St Augustine Campus, Trinidad "Professor Lal has made a most distinguished contribution to scholarship on Indian indentured labour in Fiji. His research is characterised by the use of new methodological approaches to the study of history, and by a comprehensive consideration of both quantitative and literary sources. In beautifully written articles, he has arrived at fresh and novel findings." Ralph Shlomowitz, Flinders University of South Australia "Professor Lal has produced a body of work which makes him the premier scholar of the Indian diaspora. His meticulous research, the depth of scholarship, the empathy, and the elegance have earned him great respect among Indian diaspora scholars. The themes covered in this book are relevant to other overseas Indian communities; and they are handled with such mastery that his reputation is secured." Clem Seecharan, University of North London "Brij Lal's Chalo Jahaji is an intensely personal journey through his life and that of the 60,000 Indians who became girmitiyas in Fiji. The intricate history is measured, but Lal reveals himself and his family in a way historians seldom do. This proud grandson of a girmitiya is equally a proud son of Fiji. Chalo Jahaji is Pacific history at its best: rigorous and critical, informative and involved." Clive Moore, University of Queensland